Analyzing the Significance of Reformed Epistemology: A Critical Review of Criticism of Evidentialism and its Implications for Evangelical Apologetics - Kristiani Yanti Kana; Delf Gustaf Kalalo (PT FORMOSA CENDEKIA GLOBAL, 2026)
Reformed Epistemology (RE) is one of the most significant developments in the philosophy of religion of the 20th and 21st centuries. This article analyzes the significance of Reformed Epistemology, focusing on its critique of evidentialism and its implications for the practice of evangelical apologetics. Through a critical literature review approach, this paper will outline the core arguments of Reformed Epistemology, particularly the thesis of